O celibato pedagógico feminino em Sergipe nas três primeiras décadas do século XX : uma análise a partir da trajetória de Leonor Telles de Menezes. - Santos, Nivalda Menezes (2006)
This paper has as objective to analyze and to understand the arguments used by Helvécio de Andrade e Rodrigues Dória in the three first decades of century XX to defend the feminine pedagogical celibacy having as starting point the personal and professional trajectory of the celibate teacher Leonor Telles de Menezes. It considers the conceptions of Roger Chartier about 'representation' and 'appropriation', of Pierre Bourdieu about field and 'social capital', of Nobert Elias about 'History' and 'Sociology', as well of Carla Simone Shamon about 'trajectory' to facilitate the use of the consulted sources, such as: bibliographical, documental, iconographic and oral. It points the mentality of the time that many women of Sergipe can't marry if they wanted to become teachers because the social pressure. The current idea was that the marriage could compromise the good course of the schools. Finally, it shows the lack of studies on teachers that, like Leonor, gave excellent services to the education of the State, although its names to remain only in the memory of relatives, friends and former-pupils.